A hand-up or a hand-out? An argument for concierge services for the development of innovation capacity in startups. (1st December 2020) - Noble, David; Charles, Michael B; Keast, Robyn
Abstract : This study suggests that a concierge service, provided by governments, can assist startups to gain streamlined access to the services, capabilities and capital required to bring innovation efficiently and cost-effectively to market. It analyses a range of concierge models in five separate jurisdictions to determine best practice. The paper develops a rationale and working definition for a concierge service that will assist public sector managers to help young high-growth SMEs and startups to navigate the increasingly complex innovation ecosystem.